ENVIRONMENTAL DETERIORATION OR ENVIRONMENTAL SUSTAINABILITY? EVIDENCE OF RENEWABLE AND NON-RENEWABLE ENERGY CONSUMPTION - Dr. Muhammad Nadeem; Sadia Masood; Ruqia Shaheen; Farrah Nayab Jehangir; Sayyed Muhammad Bilal (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The study analyzes the impact of renewable and non-renewable energy on the environmental conditions of developing nations in three Asian regions. To meet the objectives, the data is taken from 1990 to 2018. The Panel-ARDL outcomes for the long run illustrate that non-renewable forms of fossil fuels deteriorate the environment. At the same time, renewable energy and economic growth endorse environmental sustainability in all three Asian regions. However, capital formation and labor productivity follow the path of non-renewables by hurting the environmental conditions of Southeast Asian, South Asian, and Central Asian emerging economies. In discussing the effects in the short run, only renewable energy and labor productivity are the factors that significantly reduce carbon emissions and lead to environmental sustainability. However, it has been noticed that the error correction term has adjusted the error by about 56 percent. Therefore, the study recommends following the sustainable path of renewable energy to attain sustainable development goals.